Synthetic photometry for M and K giants and stellar evolution: hydrostatic dust-free model atmospheres and chemical abundances. Issue 4 (27th January 2016) - Aringer, B.; Girardi, L.; Nowotny, W.; Marigo, P.; Bressan, A.
Abstract : Based on a grid of hydrostatic spherical comarcs models for cool stars, we have calculated observable properties of these objects, which will be mainly used in combination with stellar evolution tracks and population synthesis tools. The high-resolution opacity sampling and low-resolution convolved spectra as well as bolometric corrections for a large number of filter systems are made electronically available. We exploit those data to study the effect of mass, C/O ratio and nitrogen abundance on the photometry of K and M giants. Depending on effective temperature, surface gravity and the chosen wavelength ranges, variations of the investigated parameters cause very weak to moderate and, in the case of C/O values close to 1, even strong shifts of the colours. For the usage with stellar evolution calculations, they will be treated as correction factors applied to the results of an interpolation in the main quantities. When we compare the synthetic photometry to observed relations and to data from the Galactic bulge, we find in general a good agreement. Deviations appear for the coolest giants showing pulsations, mass-loss and dust shells, which cannot be described by hydrostatic models.